Marketing Strategy of Animal Feed for Laying Hens (Case Study of PT. Cahaya Mario Brother Group) - Aisyah; Asrar; Ilham Ahmad (Indonesian Journal of Economic & Management Sciences, 2023)
This study aims to determine marketing strategies and analyze internal and external factors that exist in PT. Cahaya Mario Brother Group. The data collection method used is participatory observation, and the data used are primary and secondary data. The data analysis methods used are qualitative descriptive and SWOT analysis. The results of this study put the company's position in quadrant I where the position in quadrant I explained that PT. Cahaya Mario Brother Group has great opportunities and strengths so that it can take advantage of the opportunities that exist. The strategy used by PT. Cahaya Mario Brother Group is a strategy that is (SO) which means supporting aggressive policies. The strategy that must be done to deal with competitors is to increase promotion and maintain product quality. This aims to increase consumer attractiveness, expand market share and reduce the risk of similar competing products